Prevalence of burnout and associated factors among midwives, 2023: institution-based cross-sectional study - Alemu, Solomon Seyife; Hajure, Mohammedamin; Agago, Mahlet Tesfaye; Hussein, Feisal; Gesisa, Hana Israel; Teferi, Sheleme Mengistu; Yohanes, Daniel; Wedajo, Lema Fikadu (Frontiers in Public Health, 2024)
Background One of the main characteristics of the mental health condition known as burnout syndrome is an overwhelming feeling of physical and emotional tiredness, particularly with regard to one’s work. Midwives are the group most prone to burnout because they work in emergency situations to save two lives at a time, share the stress of laboring women, and put in extra hours without enough payment. Besides this, there is little information on burnout among Ethiopian midwives. Objectives To assess burnout and associated factors among midwives working in public health facilities in West Arsi Zone, Ethiopia. Methods and materials A census method cross-sectional study was conducted among all 467 midwives working in public health facilities found in the West Arsi Zone, Ethiopia, from September 1 and 30, 2023. A pretested, validated face-to-face interviewer-administered structured questionnaire was used to collect data. Then, binary logistic regression was used for analysis. Bi-variable and multivariable logistic regression analyses were employed to identify factors associated with burnout. The level of statistical significance was declared at p < 0.05 with a 95% CI. Results Overall, the prevalence of burnout among midwives was 47.10% (95% CI: 42.55, 51.75%). Marital status not in union 2.03 (95% CI: 1.32–3.13), working more than 40 h per week 2.00 (95% CI: 1.29–3.08), conflict with their metron 2.33 (95% CI: 1.54–3.54), not satisfied with their current job 2.39 (95% CI: 1.56–3.66) and having depression symptoms 1.71 (95% CI: 1.06–2.74) were factors significantly associated with burnout. Conclusion This study found that in the study area, almost half of the midwives experienced burnout. Thus, it is recommended that midwives should develop respectful interactions with both their mentors and colleagues. Secondly, we suggest that zonal health offices set up systems that by shortening working hours and boost job satisfaction by creating conducive working environment, provide opportunities for career advancement and increase employee engagement.